Investigation of Geogrid Aperture Size Effects on Subbasesubgrade Stabilization of Asphalt Pavements - Tuba Sert; Muhammet Vefa Akpınar (The Baltic Journal of Road and Bridge Engineering)
The increased use of geogrids in highway pavement subbase layer reinforcement applications has resulted in a need to better understand the soil–geogrid interface properties for the use in analysis and design. For this purpose, a series of laboratory large scale pullout tests was carried out with three different aperture size geogrid samples randomly sampled from a single manufacturer. It was found that geogrids are unique in their pullout performance within pavement subbase layer structure based on their aperture sizes. Analysis indicates a strong relationship between pullout performance and geogrid aperture size of geogrids at moderate normal stress levels. Such findings aid in selection of appropriate geogrid types for subgrade and subbase interface reinforcement purposes. Further experimental analysis was conducted to investigate the wide-width tensile test performance for the same samples used in the pullout tests in this study.